Analog to digital meter reader converter using signal processing technique - Hasliza, Abu Hassan; Azlee, Zabidi; Ihsan, Mohd Yassin (Institute of Electrical and Electronics Engineers Inc., 2021)
The need for the Internet of Things to link devices and equipment, mostly in industry, is compelling industrial players to ensure they are adequately equipped with such technology. For newly established industries, it is prudent to begin by equipping their facilities with IoT-enabled technology that is widely accessible on the market. However, for older businesses, building and machine, the changeover process may be expensive, requiring them to replace existing equipment with new IOT-ready technology. A way to do this is to enhance the existing equipment without having to replace it. We suggested a solution in this article to an issue with analogue meters. The analogue reading is converted to digital using an image processing method. Thus, the digital readings can be sent to an IOT platform, allowing for effective asset monitoring.